Evaluasi Usability dan Perbaikan Antarmuka Pengguna Situs Web VEDC/P4TK BOE Malang Menggunakan Questionnaire For User Interface Satisfaction (QUIS) dan Pendekatan Human-Centered Design - Mochamad Arief Satriajaya; Hanifah Muslimah Az-Zahra; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
VEDC / P4TK BOE Malang is an institution that since 1986 training conducted in the field of development and improvement of competence. P4TK BOE Malang, is an integrated part of the Ministry of Education and Culture as a technical implementation unit of the Directorate General Teachers and Education Personnel. The frequent problems of users encourage VEDC agencies to make detailed implementation on the website. User improvements are made to resolve issues that are often conveyed by the user. User improvements are made using Human-Centered Design. Usability aspects that are in testing, among others; Efficiency for an efficient level of website access, Effectiveness for measuring success rate, and Questionnaire Questionnaire for User Interaction Satisfaction (QUIS) for Measuring Satisfaction. The preliminary evaluation was carried out by conducting a usability test which resulted in 8 sections with the result of QUIS questionnaire interview. Evaluation is done by the same method to design prototype designed by overcoming the initial design problem. Evaluation gives back-up on time from 328 seconds to 214 seconds, success rate from 68.3% to 100%, error rate from 29.1% to 0%, and quality level from score 147 to 232 with max value of 270